Da captura e do incapturável: considerações sobre funk, capitalismo e desejo - Oliveira, Thaina de Paula (2020)
The present study was developed from the questioning about the relationship between funk and the discourses of domination prevailing in Brazilian society, given its importance and unique position in culture. To this end, we explored two ways that could broaden the debate on the subject. The first one was to establish relations between funk, as culture, and the capitalist way of production and hegemonic culture from the structural axes: class, race and gender. The second was to investigate from a psychoanalytical perspective what things the genre, as both a creative process and a way of life, can teach about the desire and uniqueness of subjects. Thus, we seek to establish a dialogue between Psychoanalysis and the fields of Cultural Studies, Art and History. For that, the first chapter consists of a presentation of the history of funk, whose objective is to highlight the heterogeneity of the phenomenon, considering its transformations and its structuring elements: music, dance and parties and to build a basis for the following discussions. In the second chapter we seek to present some notions pertaining to the field of Cultural Studies, the relations between industry and culture, based on the notion of culture as a field of dispute between a block of power, that determines which are the manifestations that should be transformed according to the values of this same block, and another block, that resists the movements of capture and total dominance. In the third chapter we intended to weave some of the articulations between the fields of art and psychoanalysis based the concept of sublimation, which was initially presented by Freud as a process present in art in artistic creation, and that constitutes a third possible destination for libido. However, it is in accordance with J. Lacan's developments for the concept presented on The Ethics of Psychoanalysis (1959-1960 / 2008), that we evolve the discussion between art, subject and desire, through the debate about of the object of das Ding, the artistic creation and the subject of desire. Finally, in the fourth chapter we seek to explore structural issues in the discussions about funk as a manifestation of culture and art, with the aim of establishing opening and closure points between the different fields of knowledge, as well as discussing possible resistances that funk may offer against the dominant discourses